2020
DOI: 10.1016/j.foodchem.2020.126293
|View full text |Cite
|
Sign up to set email alerts
|

Measuring quantitative proteomic distance between Spanish beef breeds

Abstract: Estimates of quantitative proteomic distance between populations have not been reported to date. Here, quantitative proteomic distances between three Spanish bovine breeds (Asturiana de los Valles, AV; Retinta, RE; and Rubia Gallega, RG) were estimated from two-dimensional electrophoresis profiles of meat samples of longissimus thoracis muscle at 2 h post-mortem. Statistically significant distances were detected between AV/RG and the most genetically different RE breed, using the novel QD measure of quantitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…RE calves showed the highest cortisol value at slaughter time, and even though we have not measured “temperament” as a feature in this research, unlike the aforementioned authors [ 47 ] have, it is well-known that the RE breed has a wilder “temperament” than AV and RG breeds, a factor that could explain this finding. However, the AV and RG breeds are improved breeds that provide easier handling and are genetically closer [ 48 ], and show the lowest cortisol levels at slaughter time.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…RE calves showed the highest cortisol value at slaughter time, and even though we have not measured “temperament” as a feature in this research, unlike the aforementioned authors [ 47 ] have, it is well-known that the RE breed has a wilder “temperament” than AV and RG breeds, a factor that could explain this finding. However, the AV and RG breeds are improved breeds that provide easier handling and are genetically closer [ 48 ], and show the lowest cortisol levels at slaughter time.…”
Section: Resultsmentioning
confidence: 99%
“…The different temperaments of the breeds under study should be noted, as was indicated above for the RE breed. In contrast, the AV and RG breeds are genetically closer [ 48 ], and their temperament is calmer, non-aggressive or reactive, particularly the RG breed [ 50 ]. Other authors [ 8 , 47 ] indicated the importance of breed on stress response, but to the best of our knowledge, there is a lack of information concerning the effect of the interaction between the farm management system and the breed on the pre-slaughter stress biomarkers.…”
Section: Resultsmentioning
confidence: 99%
“…The quantitation of statistically significant changes of protein abundance ( p value < 0.05) between potato cultivars was assessed by FC and RC statistics ( Table 3 ). It can be seen that FC is less useful than RC as a general measure of quantitative changes of proteins among sample groups, as previously shown [ 39 , 42 , 57 , 58 ]. The FC measure takes values of −∞ or +∞ for unshared (or unique) protein spots among sample groups, whatever their difference in volume.…”
Section: Resultsmentioning
confidence: 64%
“…1A vs. 1B). Therefore, 2-D DIGE would be an advantageous alternative to study and compare the effect of ageing in meat from different breeds or muscles, where a higher inter-sample variability would be expected due to intrinsic proteome differences among breeds and muscles [31,32].…”
Section: Discussionmentioning
confidence: 99%